Distress and unemployment: The related economic and noneconomic factors in a sample of unemployed adults - Frasquilho, Diana (2016)
Objectives To examine the associations between economic and noneconomic factors and psychological distressin a group of 748 unemployed adults during economic recession. Methods Data were collected through a questionnaire. Bivariate and logistic regression analyses were used to test the associations between distress and the deprivation of income and latent benefits of employment (time structure, activity, status, collective purpose and social contact). Results The participants’ mean of distress was higher than the national population mean, and 46.5% of the participants scored above that. All economic and noneconomic factors emerged as strong predictors of distress; particularly financial deprivation (OR 1.06; CI 95 % 1.04–1.09) and lack of structured time (OR 1.07; CI 95 % 1.05–1.09). Women (OR 1.40; CI 95 % 1.04–1.86) and people with lower education levels (OR 0.45; CI 95 % 0.34–0.61) were more affected. Conclusions The unemployed individuals score high on distress, especially those facing financial strain and lack of structured time, and women and individuals with lower education in particular. Given the recessionary context and high unemployment rates, these insights raise awareness for policies and actions targeting the needs of unemployed people.